Complete mitogenomes of five ecologically diverse Australian freshwater fishes. Issue 1 (2nd January 2019) - Schmidt, Daniel J.; McDougall, Carmel
Abstract: Complete mitochondrial genome sequences were determined for five species of Australian freshwater fishes, representing a diverse range of ecologies and life histories. Mitogenomes were sequenced and annotated for Craterocephalus stramineus (Atherinidae); Hypseleotris klunzingeri (Eleotridae); Lovettia sealii (Galaxiidae); Leiopotherapon unicolor (Terapontidae) and Nematalosa erebi (Clupeidae). The five new mitogenomes each share the typical vertebrate mitochondrial arrangement of 13 protein coding genes, 22 tRNA genes, two rRNA genes and a control region. These sequences will be a useful resource for studies of evolutionary relationships and for management applications.